Chile : obstáculos políticos de la democratización y malestar de la sociedad - Salinas Figueredo, Darío (El Colegio de México, 2014)
In Chile, during the post dictatorship period, there has been a rising development of diverse expressions of social unrest. These expressions can be linked to citizens’ disapproval and lack of confidence towards Chilean representative institutions and to the content of the social mobilizations. Yet, the affirmations and positive diagnoses of the Chilean model persist. What do these contrasting expressions conceal? This paradox hides the significant obstacles that curb the country’s democratization; among them, the institutional design, the electoral system and the social background of the political system, embedded in social asymmetries, which have deepened, making way for rejection and alternate approaches. The electoral defeat of the “Concertación” suggests the end of one cycle and the beginning of a new one, in which, under new circumstances, the unresolved social and political problems reappear. One phenomenon that has set off the social unrest is that the unsolved problems stand out in contrast to the model, making them visible to citizens in a novel manner